Compliance with supportive periodontal therapy and its relation to the bleeding index - Novaes Jr., Arthur B.; Reno de Lima, Fernando [UNESP]; Novaes, Arthur B. (Wiley, 1996)
THIS IS A RETROSPECTIVE STUDY of 418 patients who received active periodontal treatment between the years of 1984 and 1990. The patients were instructed to return for supportive periodontal treatment (SPT) at 3 to 6-month intervals. The objective of this study was to evaluate patient compliance with periodic recall visits, and to study the relationship of bleeding upon probing in those who returned regularly. The patients were divided into 3 groups: patients who returned periodically for supportive treatment, patients who interrupted the proposed maintenance treatment, and patients who never returned after active periodontal treatment. Analysis was made for each group to correlate the degree of compliance with gender, disease classification, and type of treatment received. To analyze bleeding upon probing, 2 groups of patients were selected: a test group with 39 patients who had attended at least 10 recall visits and participated in the study for more than 40 months, and a control group of 21 patients who interrupted the SPT for at least 12 months. The results showed that 26% of the treated patients returned for SPT and, of those, 40% returned irregularly. There was a statistical significant difference in compliance in relation to disease classification and the type of treatment received, but no correlation was found between compliance and gender. There was a statistically significant difference in compliance between the test group and the control group in relation to the variation of the bleeding index.
Keywords: Bleeding index; Follow-up studies; Patient compliance; Periodontal diseases/therapy; adolescent; adult; classification; female; gingiva bleeding; hospital management; human; male; middle aged; patient; patient compliance; periodontal disease; periodontics; retrospective study; sex difference; treatment refusal; Adolescent; Adult; Appointments and Schedules; Female; Gingival Hemorrhage; Humans; Male; Middle Aged; Patient Compliance; Patient Dropouts; Periodontal Diseases; Periodontal Index; Retrospective Studies; Sex Factors; Treatment Refusal